Global epidemiology of invasive meningococcal disease - Jafri, Rabab Z; Ali, Asad; Messonnier, Nancy E; Tevi-Benissan, Carol; Durrheim, David; Eskola, Juhani; Fermon, Florence; Klugman, Keith P; Ramsay, Mary; Sow, Samba; Zhujun, Shao; Bhutta, Zulfiqar A; et al. (Population health metrics, 2013)
Neisseria meningitidis is one of the leading causes of bacterial meningitis globally and can also cause sepsis, pneumonia, and other manifestations. In countries with high endemic rates, the disease burden places an immense strain on the public health system. The worldwide epidemiology of invasive meningococcal disease (IMD) varies markedly by region and over time. This review summarizes the burden of IMD in different countries and identifies the highest-incidence countries where routine preventive programs against Neisseria meningitidis would be most beneficial in providing protection. Available epidemiological data from the past 20 years in World Health Organization and European Centre for Disease Prevention and Control collections and published articles are included in this review, as well as direct communications with leading experts in the field. Countries were grouped into high-, moderate-, and low-incidence countries. The majority of countries in the high-incidence group are found in the African meningitis belt; many moderate-incidence countries are found in the European and African regions, and Australia, while low-incidence countries include many from Europe and the Americas. Priority countries for vaccine intervention are high- and moderate-incidence countries where vaccine-preventable serogroups predominate. Epidemiological data on burden of IMD are needed in countries where this is not known, particularly in South- East Asia and Eastern Mediterranean regions, so evidence-based decisions about the use of meningococcal vaccines can be made.